2021
DOI: 10.1021/acsami.1c02855
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Exchange Coupling in NiO-Based Bimagnetic Heterostructured Nanocrystals

Abstract: A series of bimagnetic heterostructured nanocrystals having an antiferromagnetic NiO core and a ferrimagnetic Mn x Ni1–x O and/or FiM Mn3O4 island nanophase overgrowth has been synthesized under varying aqueous solution pH conditions. The two-step self-assembly process employs a thermal decomposition method to synthesize NiO nanoparticles, followed by growth of the Mn x Ni1–x O and/or Mn3O4 nanophase over the NiO core using hydrothermal synthesis at pH values ranging from 2.4–7.0. The environmentally benign hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 48 publications
6
12
0
Order By: Relevance
“…Similarly, a drastic increase of the Néel temperature of FeO even beyond room temperature was observed for a nanoscale layer magnetically coupled to adjacent ferromagnetic Fe layers . Very recently, ferrimagnetic properties were indicated by DFT-based calculations for a mixed Mn x Ni 1– x O phase in the vicinity of NiO . A similar scenario might be attributed to our nanoscale rock-salt nanoparticle core surrounded by a ferrimagnetic spinel shell, supporting an ordering temperature above the ambient temperature of our magnetic SANS experiment.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, a drastic increase of the Néel temperature of FeO even beyond room temperature was observed for a nanoscale layer magnetically coupled to adjacent ferromagnetic Fe layers . Very recently, ferrimagnetic properties were indicated by DFT-based calculations for a mixed Mn x Ni 1– x O phase in the vicinity of NiO . A similar scenario might be attributed to our nanoscale rock-salt nanoparticle core surrounded by a ferrimagnetic spinel shell, supporting an ordering temperature above the ambient temperature of our magnetic SANS experiment.…”
Section: Resultssupporting
confidence: 87%
“…79 Very recently, ferrimagnetic properties were indicated by DFT-based calculations for a mixed Mn x Ni 1−x O phase in the vicinity of NiO. 80 A similar scenario might be attributed to our nanoscale rock-salt nanoparticle core surrounded by a ferrimagnetic spinel shell, supporting an ordering temperature above the ambient temperature of our magnetic SANS experiment. In the antiferromagnetic phase of the binary compounds, rhombohedral (FeO) and tetragonal (CoO) crystallographic distortions have been observed that can serve as signatures for magnetic ordering.…”
Section: ■ Results and Discussionsupporting
confidence: 76%
“…During hydrothermal synthesis, Mn 2+ and Mn 3+ ions are adsorbed on the NiO surface, competing with the highly reactive OH − ions present in the aqueous solutions. The adsorption of the metal ions on the NiO surface is controlled via the protonation and deprotonation processes, and thereby pH, as described in more detail in our previous work [26]. Accordingly, pH has a direct affect on the structural composition of the overgrowth phase and defect properties of the core/overgrowth interface [27][28][29].…”
Section: Introductionmentioning
confidence: 95%
“…We have been able to manipulate such effects in our previous work on AFM/FiM coupled Cr2O3/MxCr2-xO3 core-shell nanoparticles [20][21][22][23][24] and (Mn3O4 and/or MnxNi1-xO)/NiO bimagnetic HNCs [25]. Our previous study demonstrated that overgrowth of Mn3O4 and/or MnxNi1-xO phases and the resulting magnetic properties are tunable using pH in the hydrothermal synthesis of (Mn3O4 and/or MnxNi1-xO)/NiO HNCs [26]. In particular, it was shown that a substantially large coercivity and exchange bias is obtainable for the Mn-NiO-based HNCs upon tuning the pH value to about 5 in the second step hydrothermal synthesis process [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation